Teori Belajar Sosial dalam Pendidikan Kristen: Teladan, Relasi dan Disipleship - Eniati Ndururu; Enjelina Enjelina; Hesty Sinaga; Rainaldi Setiawan; Hisardo Sitorus (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
This paper aims to examine the relationship between Social Learning Theory and the principles of Christian education, particularly in character formation and the discipleship process. Social Learning Theory asserts that human behavior is shaped through observation, imitation, and social interaction, thus role models and the environment play a central role in the learning process. This understanding aligns with Christian education, which emphasizes that faith and character are developed through relationships, life experiences, and role models, as demonstrated in God's relationship with Israel, the life of Jesus Christ, and the practices of the early church. The integration of these two approaches demonstrates that effective Christian character formation requires a combination of modeling, mentoring, and a supportive community, along with the spiritually renewing work of the Holy Spirit. Thus, modern psychological theory and the principles of faith education can complement each other to create a holistic approach to Christian education, whether in the church, school, or family.